An enriched medical home intervention using community health workers improves adherence to immunization schedules. Issue 46 (17th November 2015) - Pati, Susmita; Ladowski, Kristi L.; Wong, Angie T.; Huang, Jiayu; Yang, Jie
Highlights: Disparities in vaccination rates among young children persist. Our enriched medical home intervention improves vaccination rates for young children. Our intervention directly integrates community health workers with the medical home. Our model may be a cost-effective way to improve vaccination rates. Abstract: Importance: Disparities in childhood vaccination rates persist. Objective: To evaluate the impact of an enriched medical home intervention using community health workers on improving immunization adherence among young children. Design: The intervention group received home visits from trained community health workers to support families in adhering to recommended care while the comparison group received usual care (i.e. no home visits/reminders). Immunization history and socio-demographic data were collected using medical records and a validated questionnaire. The doubly robust estimation of risk difference, which combines weighting via propensity score and outcome regression model, was used to compare immunization adherence rates between two groups. Setting: Primary care practices affiliated with a suburban tertiary care academic medical center serving a socioeconomically diverse population. Participants: The study sample included children ≤2 years of age at enrollment who crossed at least one age time point of 3, 7, 15, or 24 months during their 6 months post-enrollment period. Main outcomes and measures: The primary outcome was age-specific immunization up-to-date status defined by CDC guidelines. The primary predictor was participation in the intervention. Results: The analysis included 201 children in the usual care group and 110 children in the intervention group. The usual care and intervention groups were divided into subgroups of newborn and infant/toddler to account for prior immunization history. After adjusting for differences in group characteristics, we found a significant absolute increase in the up-to-date immunization likelihood for both newborns (20.9%, p = 0.01) and infants/toddlers (16.8%, p = 0.01) receiving the intervention when compared to their peers receiving usual clinical care. Conclusions and relevance: Our findings demonstrate the positive impact of an enriched medical home intervention using community health worker home visitation on early childhood immunization up-to-date status. With further study, this model may provide a cost-effective approach to improving childhood vaccination rates, especially for vulnerable groups.